Conquering the IoT Frontier: Challenges Faced in India - Mayur Kesari; Neelu Kewat (International Journal of Information Security Engineering, 2024)
The internet of things (IoT) represents a transformative force reshaping the landscape of connectivity and communication, ushering in an era marked by seamless machine-to-machine interactions and the fluid exchange of data across diverse devices and systems. This paper undertakes an extensive exploration of the prevailing state of IoT advancement within India, with a particular emphasis on delving into the multifaceted realms of security concerns, inherent challenges, and burgeoning opportunities. By scrutinizing the nuanced intricacies of IoT deployment in the Indian context, this study endeavors to furnish a comprehensive overview, elucidating the distinct risk factors and security intricacies endemic to the Indian milieu. Through a meticulous examination of these complexities, this paper aims to furnish stakeholders with a profound understanding of the obstacles impeding the widespread adoption of IoT technologies in India, thereby paving the way for informed decision making and strategic interventions. By elucidating the current landscape of IoT development, this paper not only identifies the challenges hindering progress but also endeavors to highlight the potential avenues for innovation and growth, thereby fostering a conducive environment for the proliferation of IoT technologies in the Indian subcontinent.
Keywords: Internet of things (IoT); IoT landscape; proliferation; security; widespread adoption